Some Properties of Contra Î¸gs-Closed Functions - Muntaha Khudair Abbass (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of this paper is to introduce and study some properties of a new generalization of contra closed  set called contra â¬gs-closed function in topological spaces, as well as  , some theorems and examples of these functions  .